Peran Serta Masyarakat Adat dalam Pengelolaan Hutan Konservasi melalui Pemberdayaan Masyarakat Berbasis pada Kearifan Lokal - Runggandini, Caritas Woro Murdiati; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
This study combined normative study and sociological study. Normative study was conducted by studying legislations which supports the participation of communities in forest resources management. Sociological studies focused on empowerment model for adat communities around forests performed in Bali Province by using community empowerment by West Bali National Park Office/TNBB. Literature data and field discoveries were analyzed qualitatively. The study discovered that the adat communities of TNBB buffer villages already had local wisdom when they interacted with forest resources around them, in the forms of awig-awig, supported by strong traditional institution. People were skillful in making harmonious synthesis between efforts to preserve forests and improving economic welfare by breeding Bali starlings. TNBB helped the communities of TNBB buffer villages to empower their economy by providing livestock breeds, plant seeds, and honeybees. Forest management in TNBB went well and effectively because the management involved the adat communities of TNBB buffer villages, was rooted on local wisdom, and had the full support of local community organizations (traditional villages). Community empowerment model which was rooted on local wisdom, supported by local community organizations, which built harmonious partnership should be developed to prosper communities and preserve forests.